2019
DOI: 10.1016/j.joms.2019.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated With Malignant Transformation in Patients With Oral Leukoplakia in a Chinese Population: A Retrospective Study

Abstract: Purpose: The study aim was to investigate the risk factors for the progression of oral leukoplakia (OLK) to malignancy.Patients and Methods: The data from 2,628 patients with OLK were retrospectively reviewed. Of these 2,628 patients, 192 had undergone sequential biopsies and were separated into 4 groups according to their final diagnosis. The risk factors were analyzed using Kaplan-Meier univariate survival analysis and Cox multivariate analysis.Results: In 41 of the 2,628 patients (1.7%), the OLK had progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 26 publications
(31 reference statements)
5
18
0
Order By: Relevance
“…Our study also found that smoking was not a significant risk factor for OL malignancy, which is in line with other studies ( 9 , 20 ). Although there are similarities in the genetic alterations found in smokers and non-smokers whose cases suffered MT into oral squamous cell carcinoma ( 27 ), previous studies have described a significantly elevated risk for malignant progression in non-smokers ( 9 , 27 - 29 ), as we observed.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study also found that smoking was not a significant risk factor for OL malignancy, which is in line with other studies ( 9 , 20 ). Although there are similarities in the genetic alterations found in smokers and non-smokers whose cases suffered MT into oral squamous cell carcinoma ( 27 ), previous studies have described a significantly elevated risk for malignant progression in non-smokers ( 9 , 27 - 29 ), as we observed.…”
Section: Discussionsupporting
confidence: 93%
“…Considering the clinical subtype of OL, our findings are in line with the literature, confirming the high potential of MT of nonhomogenous leukoplakia ( 11 , 20 , 21 ). Although there is a consensus that PVL has a MT rate higher than 60% ( 9 , 11 , 22 ), we found a MT rate of only 8% among the cases described as PVL.…”
Section: Discussionsupporting
confidence: 91%
“…c If a patient has other sites of oral leukoplakia in addition to tongue, the patient will be categorized as "yes" malignant changes of OLK, similar conflict between the published reports was also found; oral habits were significant factors in some academic works [5,29,39] and non-significant in others [21,38,[40][41][42]. In the present study, oral habits were not factors related to the recurrence or malignant transformation of oral tongue leukoplakia.…”
Section: Discussionsupporting
confidence: 68%
“…The relationship between a history of head and neck cancer in the context of postoperative recurrence and malignant transformation has been studied in several studies [23,[29][30][31][32]. In a cross-sectional study of prevalence and risk factors of carcinoma and dysplasia in 1046 patients with OLK in Taiwan, a history of head and neck cancer was not a factor related to the presence of dysplasia or carcinoma in the pathological diagnosis of OLK [16].…”
Section: Discussionmentioning
confidence: 99%
“…2 According to its pathological features, OLK can be divided into epithelial hyperplasia or hyperkeratosis, with or without epithelial dysplasia. 3 The probability of malignant transformation of OLK was 0.13-17.5% in one study, which was proportional to the degree of epithelial cell dysplasia. 4 Oral epithelial cell dysplasia (OED) had malignant conversion rates of 6.6%-36.4%, which may increase the risk of OLK malignant transformation.…”
Section: Introductionmentioning
confidence: 93%